2022
DOI: 10.21608/ejbo.2022.84745.1732
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Genetic Diversity of Some Species of Genus Vicia Using ISSR and ITS Molecular Techniques

Abstract: T HE HIGH economic importance of the genus Vicia has led to a large body of studies on the molecular characterization and investigation of phylogenetic relationships among species that belonged to this genus. The Mediterranean area is the principal center of distribution and diversification where polymorphism has been associated with the geographical origin of germplasm (ICARDA, 2013). The extent of genetic diversity in germplasm can be assessed through morphological characterization and genetic markers. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
1
0
0
Order By: Relevance
“…Furthermore, regarding the Shannon diversity index, SCoT analysis revealed an average of 0.220, while in other studies, the average was 0.63 for SSR markers [42], 0.41 for ISSR markers [26] and 0.29 for RAPD markers [43]. The results of our study are really close to the results reported by [47]. They studied the genetic diversity of some species of genus Vicia using ISSR and ITS molecular techniques.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, regarding the Shannon diversity index, SCoT analysis revealed an average of 0.220, while in other studies, the average was 0.63 for SSR markers [42], 0.41 for ISSR markers [26] and 0.29 for RAPD markers [43]. The results of our study are really close to the results reported by [47]. They studied the genetic diversity of some species of genus Vicia using ISSR and ITS molecular techniques.…”
Section: Discussionsupporting
confidence: 87%
“…Many publications have successfully used the ISSR technique to confirm genetic diversity and discover somaclonal variations of many plant species, including tea (Devarumath et al, 2002), date palm (Ahmed et al, 2012), Picorriza kurroa (Rawat et al, 2013), Artemisia absinthium (Kour et al, 2014), sugarcane (Thorat et al, 2017;Shingote et al, 2019) and Vicia (El-Badan et al, 2022). ISSR has also been used to detect polymorphism produced by EMS in tissue culture grown plants (Perera et al, 2015).…”
Section: Introductionmentioning
confidence: 99%